Characterization of Motor Performance in 200 Normal Ankles Through Isokinetic Evaluation. Issue 1 (January 2022) - Mansur, Nacime S.; Fonseca, Lucas; Maciel, Eduardo S.; Inojossa, Thiago; Netto, Cesar de Cesar; Astur, Diego C.
Category: Ankle; Sports Introduction/Purpose: The isokinetic test has been used diffusely as a way to evaluate the functional results after the rehabilitation of musculoskeletal injuries. In the ankle, in particular, most studies are related to lateral ligament injuries and Achilles tendon's injuries. However, different protocols are used and a lack of normative values is observed in the literature. The aim of this work is to perform a global isokinetic evaluation on healthy ankles in order to propose reference values for future patients. Methods: We evaluated 100 participants (200 ankles) using the Biodex 3 System for the eversion, inversion, dorsiflexion and plantar flexion movements of the ankle. The sample consisted of individuals aged 20-60 years, with an active life and practice of recreational physical activity (non-athlete) and without previous injuries. Five repetitions for strength (N / m) and work (J) at a speed of 30° / sec and 10 repetitions for power (W) at a speed of 120° / sec were performed in our protocol. Agonist / antagonist ratio and the Muscle Deficiency Index, which globally assesses the balance between the sides for each movement, were also evaluated, as well as the demographic variables. Different statistical analyzes were performed for each parameter. Results: The mean age was 38.5 years and BMI 25.8 (CI 2.7 and 0.8 respectively). The non-dominant side was consistently stronger (higher peak torque) in all movements (p <0.001 -). The mean values obtained for force in each movement were 29.9N / m (CI 1.4) for eversion, 34.8N / m (CI 1.6) for inversion, 48.6N / m (2.0) for dorsiflexion and 140.2 N / m (CI 6.1) for plantar flexion. There was no correlation between age or BMI with the maximum torque (N / m). The ratio of eversors / inverters was 88.8% (CI 3.1) and that of dorsiflexors / plantar flexors was 36.1% (1.3). The Muscle Deficiency Index showed a balance between the sides for each movement (p 0.062), with an average global difference of less than 10% between them (eversion 8.66 [CI 3.17], inversion 4.2 [3, 48], dorsiflexion 3.41 [3.04] and plantar flexion 5.18 [2.51]. Conclusion: As far as we know, this is the largest isokinetic assessment of normal ankles ever performed. The sample, although not stratified, was considered homogeneous (coefficient of variation <50%), which allows to propose several normative values for a non-athlete population in the isokinetic evaluation. It would be interesting to compare these data in the future with the functional results in patients after the treatment of certain injuries.